(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: This research aimed to examine the effect of thyme essential oil (EO) aroma inhalation compared to placebo on anxiety levels in type 2 diabetic patients referred to the Parsian Diabetes Clinic in Tehran. Methods: In this double-blind randomized clinical trial study, 60 patients referred to the diabetes clinic were divided into an anxiety treatment group with thyme EO aroma inhalation and a paraffin (control) group. Anxiety before and after intervention and follow-up was measured using Beck's Anxiety Inventory (BAI). Data were analyzed using SPSS version 26 software. Results: The average anxiety scores decreased in the posttest and follow-up compared to the pretest (P < 0.05, F = 37.91). The data indicated that the anxiety scores were significantly different in the experimental and control groups in the posttest and follow-up compared to the pretest (F = 24.67, P < 0.05). Conclusion: According to our results, thyme EO inhalation can reduce anxiety in type 2 diabetic patients.